2014
DOI: 10.1093/jac/dku509
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with boosted PIs as an ART simplification strategy in clinical practice

Abstract: The virological efficacy of darunavir/ritonavir and lopinavir/ritonavir monotherapy is high in clinical practice. Treatment discontinuation due to safety issues is more frequent with lopinavir/ritonavir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
5
15
0
Order By: Relevance
“…Most clinicians / patients selected darunavir although a sizeable minority (14%) used lopinavir. We did not see a difference between darunavir and lopinavir in virological rebound which is consistent with observational studies of PI monotherapy [6,8,25]. Two small trials have randomised patients to either lopinavir or darunavir monotherapy and reported no difference in virological failure [26,27].…”
Section: Discussionsupporting
confidence: 84%
“…Most clinicians / patients selected darunavir although a sizeable minority (14%) used lopinavir. We did not see a difference between darunavir and lopinavir in virological rebound which is consistent with observational studies of PI monotherapy [6,8,25]. Two small trials have randomised patients to either lopinavir or darunavir monotherapy and reported no difference in virological failure [26,27].…”
Section: Discussionsupporting
confidence: 84%
“…Our cohort had a median baseline CD4 count of 455 cells/mm, 3 lower than the averages reported in the other clinical studies, which were between 541 and 608. 18,19,2123 The median nadir CD4 count of 180 was within the range found in the clinical studies (medians were between 155 and 238). 1821,23 We did not find an independent association between CD4 count and failure, as did four of the observational studies.…”
Section: Discussionsupporting
confidence: 78%
“…18,19,2123 The median nadir CD4 count of 180 was within the range found in the clinical studies (medians were between 155 and 238). 1821,23 We did not find an independent association between CD4 count and failure, as did four of the observational studies. 18,20,21,23 One study found an association between a nadir CD4 of <200 cells/mm 3 and virological failure.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…5A). In fact, DRV/RTV (DRV/r) monotherapy has been examined in HIV-1-infected patients (57)(58)(59)(60), and the monotherapy regimen proved to be a potential long-term strategy to avoid nucleoside/nucleotide analogue toxicities and to reduce costs. Even though the protease dimerization inhibition activity of GRL-015, -085, and -097 was moderate compared to that of DRV (Fig.…”
Section: Discussionmentioning
confidence: 99%